(untitled) (Journal of Energy and Safety Technology (JEST), 2025)
The construction sector is always seen as an extremely dangerous business because of the complexity of the work involved in. In Malaysia, the non-fatal occupational injuries in the construction sector increased by 59.65% in 2022 compared to the previous year. Additionally, with 6.30 deaths per 100,000 workers, the construction industry has the greatest risk of worker fatalities. Due to the construction sector consistently reporting the highest number of fatal accidents among all industries in Malaysia, this study will specifically focus on identifying the underlying factors that influence occupational injuries in this sector. On the other hand, the government implemented the new OSHA amendment in June 2024. It is essential to assess the beneficial impact of the latest amendment act. The effectiveness of risk assessments stands as another critical area of this study. A total of 90 respondents were involved in this study. Questionnaires were distributed to construction workers to obtain data. Subsequently, a set of quantitative analysis was performed in order to analyze the variables. The study employed several statistical analyses, including T-test, Analysis of Variance (ANOVA), Pearson Correlation, Multiple Linear Regression (MLR) and Linear Regression. Results: This study identified that economic pressure and safety investment are significant contributory factors of occupational injury. The enforcement of new OSHA amendments and workplace risk assessments contributed to significantly lower numbers of injuries and improved safety performance in the construction industry. The present study has addressed the research gap concerning the key factors contributing to occupational injuries in the Malaysian construction industry and the effectiveness of the new OSHA (2022) amendments.